Towards a modern Europe [videorecording] the Renaissance - Dooley, John.; International Film Bureau (London Polomis Films, 1974)
An examination of major events and figures in Europe during the Renaissance including the Reformation, the discovery of the new world and the Sun King, Louis XIV of France.
VHS.
Keywords: Renaissance; Humanism; Europe -- History -- 1492-1648.